2023
DOI: 10.1021/acsnano.2c10593
|View full text |Cite
|
Sign up to set email alerts
|

Reconfigurable Two-Dimensional Air-Gap Barristors

Abstract: Reconfigurable logic circuits implemented by two-dimensional (2D) ambipolar semiconductors provide a prospective solution for the post-Moore era. It is still a challenge for ambipolar nanomaterials to realize reconfigurable polarity control and rectification with a simplified device structure. Here, an air-gap barristor based on an asymmetric stacking sequence of the electrode contacts was developed to resolve these issues. For the 2D ambipolar channel of WSe 2 , the barristor can not only be reconfigured as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 50 publications
0
16
1
Order By: Relevance
“…In this sense, Zhang et al have reported that 2D semiconductors can be electrostatically doped by applying gate-voltages despite the existence of air gap at the metal-2D semiconductor junction. [33] Therefore, although the existence of the air gap at metal-MoS 2 junction may affect the top-gate performance, the electrostatic modulation of R C and R jun by V TG is still possible. S5 (Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this sense, Zhang et al have reported that 2D semiconductors can be electrostatically doped by applying gate-voltages despite the existence of air gap at the metal-2D semiconductor junction. [33] Therefore, although the existence of the air gap at metal-MoS 2 junction may affect the top-gate performance, the electrostatic modulation of R C and R jun by V TG is still possible. S5 (Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…To investigate the impact of V TG on R C , we fabricated DG MoS 2 FETs with Sb (and DG MoS 2 FETs with Ti as a reference) electrodes on a global bottom‐gate (BG) silicon substrate capped with 285 nm SiO 2 (To ensure the screening effect of metal electrode against V TG , total thickness of ≈25 nm is used). [ 33 ] The TG of the device is formed by an exfoliated hBN flake (≈50 nm) with a TG electrode of Ti/Au (5/70 nm). The detailed fabrication process is described in the Experimental Section.…”
Section: Resultsmentioning
confidence: 99%
“…The identical nanosystem was also applied for a photothermal/NO-based combined therapy. 259 The NIR afterglow produced under ultrasound irradiation activated PDA layers to liberate NO and induces a photothermal effect. The liberation of NO and the temperature gradient on the NPs caused them to self-propel, enhancing endocytosis into tumour cells by 2 fold.…”
Section: Ultrasound-excited Mechanoluminescencementioning
confidence: 99%
“…33 The Schottky barrier can also form when there exists an air gap around the interface between the flake and bottom electrodes. 34 The Schottky barrier may vary from contact to contact, giving rise to a moderate rectification effect of the AC current from source to drain. As a result, the net current passing through the sample consists of both DC and AC components, as illustrated in Figure 4(g).…”
mentioning
confidence: 99%
“…An effective DC bias might be induced by passing the AC current through nonideal contacts with Schottky barriers. Such barriers occur at source and drain electrodes contacting NbSe 2 , as a result of charge transfer between them due to a difference in work functions of Au (4.7 eV) and NbSe 2 (5.9 eV) . The Schottky barrier can also form when there exists an air gap around the interface between the flake and bottom electrodes . The Schottky barrier may vary from contact to contact, giving rise to a moderate rectification effect of the AC current from source to drain.…”
mentioning
confidence: 99%